The Evolution of Multiple Jobholding in the U.S. Labor Market: The Complete Picture of Gross Worker Flows - Etienne Lalé (Institute for the Study of Labor (IZA), 2016)
The U.S. labor market experienced a more than 20 percent reduction in the share of workers holding multiple jobs over the past 20 years. While this substantial trend is receiving increasing attention, the literature lacks a comprehensive picture of the gross worker flows that underlie the evolution of multiple jobholding. In this paper, first we construct new estimates of worker transitions into and out of multiple jobholding based on a Markov chain model that addresses several measurement issues. In particular, we show that time-aggregation bias cannot be ignored, as has been done in previous studies: workers typically hold a second job for a short period of time, which imparts a large bias in the estimates of transition probabilities. We go on to conduct a decomposition of the downward trend in multiple jobholding into the evolution of the underlying worker flows. This decomposition indicates that the trend is overwhelmingly explained by the dwindling propensity of full-time workers to take on a second job. We view the decrease in multiple jobholding as another manifestation of the changing labor supply behavior of U.S. workers observed during the past decades.
Keywords: E24; J21; J22; J60; 330; multiple jobholding; worker flows; trend decomposition